Written interprofessional communication in the context of home healthcare: A qualitative exploration of Swiss perceptions and practices. Issue 3 (3rd July 2019) - Junod Perron, Noelle; Le Breton, Julien; Perrier-Gros-Claude, Olivier; Schusselé Filliettaz, Séverine; Hudelson, Patricia; Pautex, Sophie
ABSTRACT: The aim of this study was to explore the practices and perceptions of Swiss home care professionals with regards to written interprofessional communication. We analyzed 11 home care notebooks and conducted six focus groups with home health-care professionals in 2015–2016. Interprofessional written communication was rarely explicit. Health professionals reported a lack of clarity about what to document and for whom. They felt unsure how to reconcile the need for confidential information-sharing among health professionals and the desire for patient/families' active involvement. An ideal (electronic) tool should allow patients to formulate goals and use the platform while allowing health professionals to communicate confidentially among themselves in order to avoid information retention.